Meteorological effects of the solar eclipse of 20 March 2015: analysis of UK Met Office automatic weather station data and comparison with automatic weather station data from the Faroes and Iceland - Edward Hanna; John Penman; Trausti Jonsson; Grant R. Bigg; Halldor Bjornsson; Solvi Sjuroarson; Mads A. Hansen; John Cappelen; Robert G. Bryant (2016)
Here, we analyse high-frequency (1min) surface air temperature, mean sea-level pressure (MSLP), wind speed and direction and cloud-cover data acquired during the solar eclipse of 20 March 2015 from 76 UK Met Office weather stations, and compare the results with those from 30 weather stations in the Faroe Islands and 148 stations in Iceland. There was a statistically significant mean UK temperature drop of 0.83 Â±